Două forme productive în anii 1990 şi 2000: eclectismul postmodern şi autoficţiunea - Cătălin Sturza (Revista de Istorie și Teorie Literară)
This article discusses two productive forms of Romanian prose of the last two decades: on the one hand, the novel that refines and moves beyond (by means of parody) the Postmodern eclecticism; on the other hand, a form borrowed in the 1990s and 2000s from the French prose by the young Romanian novelists of 2000 – generically known as Autofiction. The article selects and analyzes three relevant novels for each of the two forms. Thus, the Postmodern eclecticism is illustrated by the Orbitor series, of Mircea Cărtărescu – which is perhaps the most debated and challenged series (by the literary criticism) of the last two decades –; Christina Domestica şi Vânătorii de suflete and Simion liftnicul. Roman cu îngeri şi moldoveni, of Peter Cimpoeşu. The Autofiction is illustrated by the debut novel of Ionuţ Chiva, 69, by Ioana Bradea’s debut novel, Băgău; and by Claudia Golea’s Vară în Siam. The six novels are discussed in the context of the international and traditional moderns that influence the two forms of fictions and in the context of the commercial elements used by the writers, looking for commercial success.